2022
DOI: 10.1111/bcpt.13760
|View full text |Cite
|
Sign up to set email alerts
|

A two‐decade review of butane toxicity as a substance of abuse

Abstract: Butane, an aliphatic hydrocarbon with explosive and flammable properties, is widely misused especially by young people. Acting as an asphyxiant gas, butane mainly targets the central nervous and cardiovascular systems. We aimed to review butane‐attributed toxicities due to its harmful use or misuse reported in a two‐decade period. We searched English‐language publications reporting butane toxicities from 2000 up to 2021 and collected data on age, gender, route and source of exposure, country of origin, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Light anesthetic effects were observed in mice exposed to 220 000 ppm (or 22%) butane for 25 min . The history of butane substance abuse in humans reports on butane primarily affecting central nervous system (CNS) and cardiac function . In human volunteers, a 10 min exposure with 10 000 ppm butane yielded some drowsiness, but no irritation was noted up to 100 000 ppm (or 10%) butane concentration with exposure for a few minutes .…”
Section: Resultsmentioning
confidence: 99%
“…Light anesthetic effects were observed in mice exposed to 220 000 ppm (or 22%) butane for 25 min . The history of butane substance abuse in humans reports on butane primarily affecting central nervous system (CNS) and cardiac function . In human volunteers, a 10 min exposure with 10 000 ppm butane yielded some drowsiness, but no irritation was noted up to 100 000 ppm (or 10%) butane concentration with exposure for a few minutes .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the present study does not explore questions regarding the causes, pre‐existing familial backgrounds, contributing characteristics or environmental factors of substance use and abuse (Joung & Chung, 2019; Joung & Saewyc, 2020; Maeng et al, 2021; Park et al, 2022) nor the various consequences in terms of mental and physical health (Evans‐Polce et al, 2021; Talley et al, 2019; Vahabzadeh & Mégarbane, 2022). Also worthy of note is that the few studies on sexual minority adults that have been conducted in Korea (Lee et al, 2021) were not directly related to the situation of adolescents, but identified the research problem, however, it served as a useful foundation for conducting research.…”
Section: Discussionmentioning
confidence: 99%
“…As the first study to focus on inhalant use among sexual minority adolescents in South Korea the results force us to undertake an examination of the factors that might contribute to the ongoing prevalence of inhalant use among this adolescent subpopulation who have been excluded from South Korea's national survey. Future studies will need to clarify such factors as the ease of access to and cheap prices of inhalants (Vahabzadeh & Mégarbane, 2022); the personal and cultural motivation for use; and the related physical and mental health issue including suicidality (Jung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations